Belief and Limont Ritual in Songkhla Province / ความเชื่อและพิธีกรรมลิมนต์ในจังหวัดสงขลา - นันทิยา ชูดำ, Nantiya Choodam / (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 2 (2559): May-August 2016, 2016)
บทคัดย่อ การศึกษาวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาความเชื่อและรูปแบบหรือกระบวนการของพิธีกรรมลิมนต์ในจังหวัดสงขลาที่ยังคงมีการประกอบพิธีกรรมอยู่อย่างต่อเนื่อง ผู้วิจัยเลือกใช้แนวคิดในเรื่องภูมิปัญญามาใช้ทำความเข้าใจความเชื่อและพิธีกรรมลิมนต์ เพราะพิธีกรรมลิมนต์เป็นผลของบริบททางสังคมวัฒนธรรม ซึ่งสะท้อนพื้นฐานรากเหง้าของคนภาคใต้ และประยุกต์ใช้แนวคิดของเดอร์ไคม์ในการศึกษาพิธีกรรมด้วยการจำแนกแยกแยะระหว่างสิ่งศักดิ์สิทธิ์ (The Sacred) กับสิ่งสาธารณะ (The Profane) และแนวคิดของวิคเตอร์ เทอร์เนอร์ในการเปลี่ยนผ่านสถานภาพ (Rite de passage) ในพิธีกรรมลิมนต์ การออกแบบวิจัยใช้ระเบียบวิธีวิจัยเชิงคุณภาพ ซึ่งสามารถอธิบายปรากฏการณ์ทางสังคมผ่านการวิเคราะห์ ตีความเพื่ออธิบายความเชื่อและพิธีกรรมลิมนต์จากมุมมองของเจ้าของวัฒนธรรมตามสภาพความเป็นจริง ผลการศึกษา พบว่า ในพื้นที่อำเภอนาหม่อม และอำเภอนาทวี จังหวัดสงขลา ซึ่งเป็นพื้นที่สนาม ยังคงมีการประกอบพิธีกรรมลิมนต์อยู่อย่างต่อเนื่อง อันเป็นผลจากความเชื่อพื้นบ้านที่มีอยู่มากมาย ได้แก่ ความเชื่อเกี่ยวกับผีบรรพบุรุษ เครื่องรางของขลัง และเวทมนต์คาถา นายมนต์และนางทรง บทร้องหรือบทบูชา และดนตรีพื้นบ้าน การเข้าทรง หลอมรวมเป็นระบบความเชื่อของลูกหลานที่มีต่อบรรพบุรุษ สะท้อนให้เห็นว่า คนภาคใต้ให้ความสำคัญกับระบบเครือญาติ การนับถือผู้อาวุโส และจิตสำนึกร่วมของสังคม  ในด้านรูปแบบหรือกระบวนการของพิธีกรรมลิมนต์ พบว่า มีความซับซ้อน ความละเอียดอ่อน รวมทั้งสอดคล้องกับระบบความเชื่อของ แต่ละพื้นที่ ดังปรากฏในรูปแบบตั้งแต่การจัดหาวันเวลา การรับขันหมากเพื่อบอกกล่าวการจัดงาน การจัดเตรียมงาน การประกอบพิธี ขั้นตอนพิธีกรรมต่างๆ นอกจากนี้ พบว่า มีการจำแนกแยกแยะพื้นที่ออกเป็นพื้นที่ศักดิ์สิทธิ์และพื้นที่สาธารณะ และแสดงให้เห็นพิธีกรรมเปลี่ยนผ่านจากพื้นที่ทั้งสอง เช่น การเปลี่ยนผ่านของนางทรงจากคนปกติไปสู่ร่างทรง และจากร่างทรงกลับมาสู่สถานภาพเดิม พิธีกรรมลิมนต์จึงไม่ได้เป็นภูมิปัญญาหนึ่งที่บรรพบุรุษได้สรรสร้าง สืบทอดความเชื่อต่อบรรพบุรุษ เชื่อในผีตายายที่ปกปักรักษาลูกหลานเท่านั้น แต่ยังเป็นสำนึกทางวัฒนธรรม ช่วยสร้างจิตสำนึกร่วมของคนในท้องถิ่นผ่านรูปแบบของพิธีกรรมศักดิ์สิทธิ์   คำสำคัญ : ความเชื่อ  พิธีกรรมลิมนต์  ผีตายาย  นายมนต์  นางทรง   Abstract The purpose of this research was to examine beliefs and formats or procedures of Limont Ritual (an ancestor worship ritual) in Songkhla Province that has been continually held by groups of local people. In this research, local wisdom concept was deployed to comprehend beliefs and the ritual itself since the ritual was influenced by socio-cultural context which reflects the origin of southern people. Furthermore, Emile Durkheim’s thought was used to study the ritual by separating the sacred from the profane while Victor Turner’s concept of liminality (Rite de passage) was brought to investigate the ritual. By this, qualitative research methodology was chosen as a research design in order to describe social phenomena through analyzing and interpreting methods for explaining facts of beliefs and Limont Ritual from insider view. The findings showed that Limont Ritual is plentifully held in Amphur Na-mom and Amphur Nathawee, Songkhla Province where local people are still carrying on the ritual. This consequence is resulted from folklores, such as beliefs of ancestor souls, talismans and magic, Nai Mont and Nang Song (a leader of the group that holds the ritual and a medium who communicates with spirits, respectively), chants and folk music, and spiritualism. These unite the descendants’ belief of their ancestors which represent that southern people give precedence to their family, pay respect to the elders, and pay attention to social consciousness. The research also found that pattern or procedures of the ritual are complexity, delicacy, and according with beliefs in different areas where the ritual is held. These could be seen in many complicated things included in the ritual, for example calculating and picking an auspicious day, getting Khan Mak (a parade procession that may include gifts, sacred things or things used in the ritual, depending on types of the ritual) from the organizer of the ritual, together with the practices and the ritual operations. Besides, Limont Ritual demonstrates the separation between the sacred area and the profane area before these two areas going through the liminality process. Nang Song, for instance, changes from an ordinary person to the medium before returning to a previous character when the ritual is finished. To summarize, it could be regarded that Limont Ritual is not only a folk wisdom of the older generation that inherits beliefs of their ancestors and Phi Ta Yai (ancestor ghosts who protect the descendants from evil) but also a cultured conscious which helps building local consciousness in the form of the sacred ritual.   Keywords: Beliefs, Limont Ritual, Phi Ta Yai, Nai Mont, Nang Song
Keywords: ความเชื่อ พิธีกรรมลิมนต์ ผีตายาย นายมนต์ นางทรง Beliefs, Limont Ritual, Phi Ta Yai, Nai Mont, Nang Song